Analisis Perbandingan Kuat Lentur Beton dengan Penambahan Accelerator - Sholahuddin, Moh (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study is to determine the Comparative Analysis of Concrete Bending with the addition of accelerator. This research method was conducted at the Laboratory of the Faculty of Civil Engineering, University of Bojonegoro. This research method is carried out experimentally. The main object of this study is high quality concrete with an accelerator mixture of 0.3% of the weight of cement and high quality normal concrete. In this study, the type of concrete studied was a type of high-quality concrete, besides that testing the bending strength of concrete was carried out at the age of 3 days, 7 days, 14 days and 28 days. The results of this study show that it is known that the addition of Accelerator by 3% (of the weight of cement per stir), affects the bending strength at the age of 3 days by 23% which is 3.47 Mpa, 7 days old by 14% which is 3.51 Mpa, 6 days old by 6% which is 3.60 Mpa, and 28 days old by 18% which is 4.18 Mpa